PERBANDINGAN LARUTAN FIKSATIF NAFS DENGAN ALKOHOL 96%-NBF 10% DALAM PEMBUATAN BLOK SEL PADA SAMPEL CAIRAN PLEURA - Dewi Inderiati; Bella Eka Pratiwi (Journal of Indonesian Medical Laboratory and Science, 2021)
Pleural fluid is a liquid located in the pleural cavity, between the pleural visceral and pleural parietal. Analysis of pleural fluid is mandatory in all cases of diseases that give rise to pleural effusion. Cytopathological test gives the first indication of malignancy in malignant effusion, one of which is by making cell block. The stages of making cell block begin with fixation to maintain the cell component and its state is close to the original. The purpose of this study was to determine the comparison of the quality of the cytopathological examination results from the manufacture of cell block using a fixative solution of Nathan Alcohol Formalin Substitute (NAFS) and alcohol 96% -NBF 10% in pleural fluid samples. Experimental research with cross-sectional research design. The results showed that 13 samples of pleural fluid preparations in cell block preparations with NAFS fixative solution and cell block preparations with 96%-NBF 10% alcohol fixative solution there was no significant difference in the morphological figure of the cells, the number of cells produced, the number of malignant cells analyzed, the absorption of staining and cytodiagnosis sensitivity. Based on the results of this study, it can be concluded that alcohol 96% -NBF 10% can be used as an alternative solution to fixative for pleural fluid samples.